Use of a Surgical Safety Checklist to Improve Team Communication. (26th August 2016) - Cabral, Richard A.; Eggenberger, Terry; Keller, Kathryn; Gallison, Barry S.; Newman, David
Abstract: To improve surgical team communication, a team at Broward Health Imperial Point Hospital, Ft Lauderdale, Florida, implemented a program for process improvement using a locally adapted World Health Organization Surgical Safety Checklist. This program included a standardized, comprehensive time out and a briefing/debriefing process. Postimplementation responses to the Safety Attitudes Questionnaire revealed a significant increase in the surgical team's perception of communication compared with that reported on the pretest (6% improvement resulting in t 79 = –1.72, P < .05, d = 0.39). Perceptions of communication increased significantly for nurses (12% increase, P = .002), although the increase for surgeons and surgical technologists was lower (4% for surgeons, P = .15 and 2.3% for surgical technologists, P = .06). As a result of this program, we have observed improved surgical teamwork behaviors and an enhanced culture of safety in the OR.